Influences of mesoscale anticyclonic eddies on the zooplankton community south of the western Aleutian Islands during the summer of 2010 - Saito, Rui; Yamaguchi, Atsushi; Yasuda, Ichiro; Ueno, Hiromichi; Ishiyama, Hiromu; Onishi, Hiroji; Imai, Ichiro (Journal of Plankton Research, 2013)
Mesoscale anticyclonic eddies have been observed south of the Aleutian Islands. Eddies farther east, in the Gulf of Alaska, are known to transport coastal water and coastal zooplankton to the offshore open ocean. The impacts of mesoscale anticyclonic eddies formed south of the western Aleutian Islands (Aleutian eddies) on the zooplankton community are not fully understood. In the present study, we describe zooplankton population structures within an Aleutian eddy and outside the eddy during July 2010. Based on the sea-level anomaly, the Aleutian eddy was formed south of Attu Island (172°54′E) in February 2010, and it moved southeastward in the next 5 months. Large oceanic copepods, Neocalanus cristatus, Eucalanus bungii and Metridia pacifica were more abundant inside the eddy than the outside. Inside the eddy, the life stage distribution of N. cristatus was more advanced than that outside, and Neocalanus spp. had accumulated more lipids. These conditions probably reflect the greater primary production in the eddy, production enhanced by nutrients advected into the eddy. The Aleutian eddy contained mostly oceanic copepods because it was formed in the offshore water and/or eddy–eddy interaction occurred after its formation. The sufficient food condition in the eddy presumably resulted in higher growth and survival rates of these oceanic copepods, resulting in the greater abundance, advanced development stages and greater lipid accumulation.